PAs in the National Guard and Reserves: Army, Navy, Air Force, Coast Guard. Issue 7 (July 2021) - Hooker, Roderick S.; Kozikowski, Andrzej; Paul, Johnny
Abstract : ABSTRACT: The role of physician assistants (PAs) in the United States extends to the Army National Guard; Air National Guard; and reserves of the Army, Navy, Air Force, and Coast Guard (collectively known as reserve components). To understand the duality of civilian-military PA roles, a census of the armed forces was undertaken, drawing on knowledgeable senior PA medical officers in each of the services. The survey was supplemented with data from the National Commission on Certification of Physician Assistants. In 2020, there were 1, 944 PAs in the five military reserve components with the majority (1, 597) in the Army. Most National Guard, Air National Guard, and Reserve PAs fill medical officer roles, drill with units, and are subject to active duty. As soldiers, sailors, and airmen, military PAs are trained in health, safety, warfare readiness, casualty, trauma, and crisis response. The tenure of a reserve component PA in the military ranged between 10.2 and 17.8 years. In their civilian roles, most PAs are licensed and clinically active—the majority report they work in family/general medicine, emergency medicine, general surgery, or orthopedic medicine and surgery. This dual-career role and responsibility suggests the utility and flexibility of the PA is broader than previously reported. The findings set the stage for additional research on healthcare professionals during times of domestic and international emergencies.